An exploration of equivalent scenarios for building facade fire standard tests. (15th July 2022) - Li, Yizhou; Wang, Zilong; Huang, Xinyan
Abstract: The building facade system is a key part of green buildings and carbon neutrality, but its fire safety is a global problem. Many large-scale facade fire standard tests are created to evaluate the fire risk of facade systems, but they are different from country to country, and their test results are difficult to compare. This study simulates five scenario-based facade fire standard tests, BS 8414-1 (UK), GB/T 29416 (China), ISO 13785-2, NFPA 285 (USA), and JIS A 1310 (Japan). Simulations explore the heat flux and temperature of spilled facade fire plume that controls the ignition and flame spread of facade fire. Under the default fire scenario, the BS 8414-1 and GB/T 29416 generate the largest heat flux (∼100 kW/m 2 ) to ignite the facade above the opening. The facade fire plume in ISO 13785-2 produces a near-constant heat flux (∼50 kW/m 2 ) for 2 m above the opening. The heat flux and plume temperature of NFPA 285 largely depend on the extra window burner, and JIS A 1310 can produce intensive heating on the facade by increasing the chamber fire heat release rate (HRR). The heat flux and temperature of spilled plume increase almost linearly with the outdoor fire HRR. Thus, by adjusting the total fire HRR, the values of facade surface heat flux, plume temperature, and ignition height can be matched to enable a fair comparison among different tests. This unique numerical work explores the equivalent façade fire scenarios for different standard tests that can guide future façade fire test development and optimization. Graphical abstract: Image 1 Highlights: Promote fire safety of facade system to achieve building carbon neutrality. Simulate the spilled fire plume for five scenario-based large-scale facade fire tests. Reveal the linear correlation between the heat flux on the facade and the outdoor fire HRR. Propose the equivalent fire HRRs to enable fair comparison among different standard tests.